Performance measurement system in higher educational institutions in Malaysia: an exploratory study of the implementation of balanced scorecard / Nagaretnam Thirumanickam and Bedah Ahmad - Thirumanickam, Nagaretnam; Ahmad, Bedah (Faculty of Accountancy, 2013)
High budget allocations for higher educational institutions have increased the responsibility and accountability of these institutions to their stakeholders. Hence issues of performance measurement and accountability have become very crucial for these institutions. It is necessary for the institutions to examine their performance measurement system to achieve organizational excellence. Traditional systems focusing on financial measures only will not suffice and thus the institutions should focus on strategic performance measurement systems including financial and non-financial perspectives. This study aims to examine the type of performance measurement system used by the faculty/department of accountancy in higher educational institutions in Malaysia. The findings of this preliminary study revealed that the perceptions of the responding institutions were in favour of a strategic performance measurement system. However the findings also showed that the institutions were not implementing their performance measurement system in a strategic manner.